Islamic definitions of selected English words in an English dictionary: students’ perspectives - Othman, Khairiah; Engku Ibrahim, Engku Haliza; Muhamad, Ainon Jariah; Mat Daud, Nuraihan (IDOSI Publication, 2013)
Dictionaries are designed to meet the needs of their users. The presence of dictionaries that address the varieties of English reflects the diversity in language use. The purpose of this study is to investigate Muslim students’ perspectives of the definitions of selected words in an English language dictionary. The study employs a qualitative method using document analysis and group discussions. The subjects are 21 Muslim postgraduate students pursuing Master degree in English language studies in an Islamic institution. The findings indicated that the students were aware that certain words have a different meaning in the Islamic context.